1976
DOI: 10.1172/jci108261
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet-initiated formation and uptake of the C5-9 complex of human complement.

Abstract: A B S T R A C T We have studied the interaction of radiolabeled complement components with normal human platelets, platelets from a patient with paroxysmal nocturnal hemoglobinuria, and rabbit platelets in the absence of known complement activators or in the presence of coba venon factor (CVF). When unwashed platelets in platelet-rich plasma, or washed platelets suspended in serum or autologous plasma, were incubated for 30 min, C3 and terminal components (C5, C8, and C9) were found to bind to them. The termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 27 publications
3
16
1
Order By: Relevance
“…The data reported in this study support the observation of Zimmerman and Kolb (34) that the platelets in PNH do not take up more C3 than normal platelets when exposed to CoVFtreated serum. However, these workers reported an increased uptake ofC8, presumably in the form ofmembrane attack complex by the platelets of one PNH patient under the same conditions.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The data reported in this study support the observation of Zimmerman and Kolb (34) that the platelets in PNH do not take up more C3 than normal platelets when exposed to CoVFtreated serum. However, these workers reported an increased uptake ofC8, presumably in the form ofmembrane attack complex by the platelets of one PNH patient under the same conditions.…”
Section: Resultssupporting
confidence: 91%
“…However, these workers reported an increased uptake ofC8, presumably in the form ofmembrane attack complex by the platelets of one PNH patient under the same conditions. We did not see any increase in the uptake of membrane attack complexes under our experimental conditions, which differed somewhat from those of Zimmerman and Kolb (34), particularly with regard to the presence of EDTA in the reaction mixture. In whole serum systems, the interactions ofthe platelets with activated coagulation factors, especially thrombin, as well as with complement components must be taken into consideration.…”
Section: Resultscontrasting
confidence: 84%
“…Briefly, antibody-sensitized sheep erythrocytes (EA) were incubated with human serum diluted in VBS++ for 60 min at 37°C. The complement-coated EA membranes (EAC) were washed three times in BEP buffer, centrifuged at 27,000 g and 4°C for 20 min, solubilized with Triton X-100 (Sigma Chemical Co.) or Zwittergent ionic detergent [3][4][5][6][7][8][9][10][11][12] (SB12, Calbiochem-Behring, La Jolla, CA) for 30 min at room temperature. The detergent-to-protein weight ratio was 40:1.…”
Section: Methodsmentioning
confidence: 99%
“…Although the MAC has been recognized for several years on lymphocytes (10), polymorphonuclear leukocytes (11), and platelets (12), its presence in diseased tissues has been appreciated only recently. Biesecker et al (13,14) demonstrated that a polyclonal antibody to MAC fixes to immune deposits in the kidney and skin of patients with systemic lupus erythematosus (SLE).…”
Section: Introductionmentioning
confidence: 99%
“…Generation of a novel thrombin dependent C5 convertase (Polly et al 1978;Polley and Nachman 1979;Zimmerman and Kolb 1976) has been described during blood coagulation, and direct activation of C5 and other complement components by thrombin has been reported (Huber-Lang 2006 and this volume).…”
Section: Pathophysiology Of Platelet Mediated Complement Activationmentioning
confidence: 99%